2004
DOI: 10.1159/000078478
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Multistep Human Hepatocarcinogenesis by CT during Intra-Arterial Contrast Injection

Abstract: Various types of hepatocellular nodules are seen in cirrhotic livers. In these nodules, two types of human hepatocarcinogenesis are now considered. One is de novo hepatocarcinogenesis and the other is the stepwise development from high-grade dysplastic nodule (DN), high-grade DN with well-differentiated HCC foci, and overt HCC. According to our analysis by CT during arterial portography (CTAP) and CT during hepatic arteriography (CTHA) and histological study, in accordance with the elevation of the grade of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 22 publications
1
82
1
4
Order By: Relevance
“…The evaluation of blood supply in a hepatocellular nodule is extremely important to characterize the lesion because there are sequential changes in the supplying vessels and hemodynamic state during hepatocarcinogenesis [200]. Studies based on the findings at CTAP and CTHA with pathologic correlation have shown that as the grade of malignancy within the nodules evolves, there is gradual reduction of the normal hepatic arterial and portal venous supply to the nodule followed by an increase in the abnormal arterial supply via newly formed abnormal arteries (neoangiogenesis) [201]. The hallmark of HCC during CT scan or MRI is the presence of arterial enhancement followed by washout of the tumor in the portal-venous and/or delayed phases [202].…”
Section: Ct Mri and Other Imaging Modalitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaluation of blood supply in a hepatocellular nodule is extremely important to characterize the lesion because there are sequential changes in the supplying vessels and hemodynamic state during hepatocarcinogenesis [200]. Studies based on the findings at CTAP and CTHA with pathologic correlation have shown that as the grade of malignancy within the nodules evolves, there is gradual reduction of the normal hepatic arterial and portal venous supply to the nodule followed by an increase in the abnormal arterial supply via newly formed abnormal arteries (neoangiogenesis) [201]. The hallmark of HCC during CT scan or MRI is the presence of arterial enhancement followed by washout of the tumor in the portal-venous and/or delayed phases [202].…”
Section: Ct Mri and Other Imaging Modalitiesmentioning
confidence: 99%
“…Hypovascular nodules associated with liver cirrhosis include low-or high-grade dysplastic nodules (HGDN), early HCCs, and well-differentiated HCCs [201,[220][221][222].There are significant overlaps in enhancement patterns on dynamic CT or dynamic MRI and in signal intensity on T2-weighted images [200,201,205]. Indeed, the noninvasive diagnostic criteria based on arterial hypervascularization in contrast-enhanced imaging techniques, published by the European Association for the study of the liver (EASL), are satisfied in only 61% of small nodules in cirrhosis [223].…”
Section: Ct Mri and Other Imaging Modalitiesmentioning
confidence: 99%
“…It is widely believed that HCC can develop in cirrhotic livers from premalignant lesions or dysplastic nodules via multi-step carcinogenesis. [74][75][76] During this process, a pathological feature called early HCC is clearly distinguished from conventional hypervascular HCC 77,78 (Fig. 8a-e).…”
Section: Advantage Of Assessing Multi-step Hepatocarcinogenesis: Assementioning
confidence: 99%
“…High-grade dysplastic nodules are hypovascularized both arterial and portal phases, while early HCC nodules may have similar arterial pattern with the surrounding parenchyma or exacerbated, and portal hypovascularization. In moderate or poorly differentiated HCC (classic HCC) tumor nutrition is performed only by neoformation vessels (abundant), the normal arterial and portal vasculature completely disappearing (Matsui 2004). This behavior of intratumoral vascularization is typical for HCC and is the key to imaging diagnosis .…”
Section: Dysplastic Nodules (Dn)mentioning
confidence: 99%